Spontaneous Findings in the Reproductive System of Sexually Mature Male Cynomolgus Macaques. (July 2022) - Vidal, Justin D.; Bhaskaran, Manoj; Carsillo, Mary; Denham, Steve; Dubay, Olivia; Laing, Steven; Manickam, Balasubramanian; Phillips, Stephanie; Werner, Jonathan; Irizarry Rovira, Armando R.
Sexually mature nonhuman primates are often used in nonclinical safety testing when evaluating biopharmaceuticals; however, there is limited information in historical control databases or in the published literature on the spontaneous findings in the male reproductive system. This review evaluated digital slides from the male reproductive tract (testes, epididymides, prostate, and seminal vesicles) in sexually mature cynomolgus macaques ( Macaca fascicularis ; n = 255) from vehicle control groups in nonclinical toxicology studies and compared the observations with body weight, organ weight, and geographical origin. The most common microscopic findings were hypospermatogenesis and tubular dilatation in the testes; inflammatory cell infiltrate, cellular debris, and decreased sperm in the epididymides; inflammatory cell infiltrate and acinar dilatation in the prostate; and corpora amylacea and atrophy in the seminal vesicles. There were a few correlative observations in animals when grouped by weight or geographical origin: animals with lower terminal body weights (<5 kg) often displayed features of late puberty despite having sperm in the epididymis, while animals originating from Mauritius had a lower incidence of inflammatory cell infiltrates than those from Southeast Asia/China. This review provides incidence, descriptions, and photomicrographs of the common spontaneous microscopic findings in the reproductive system of mature male cynomolgus macaques.